Hak Waris Anak Yang Lahir Dari Perkawinan Semarga Pada Masyarakat Adat Batak Toba di Perantauan - Rahmawati Emma Audrya Agustine (Notaire, 2026)
Basically, marriage in the Batak Toba indigenous community adheres to an exogamous marriage system and is carried out through honest marriage, with the aim of continuing the lineage, clan, and kinship. In its development, some of the Batak Toba indigenous community in exile have carried out same-clan marriages due to several factors. Therefore, this study will discuss the development of same-clan marriages among the Batak Toba indigenous community living abroad. The research questions in this study are the position of same-clan marriages among the Batak Toba indigenous community living abroad and the inheritance rights of children born as a result of same-clan marriages among the Batak Toba indigenous community living abroad. This study uses a legal research type with a legislative approach that refers to several laws and regulations related to the research topic, a conceptual approach that looks at the views and doctrines that have developed in law, and case studies related to the research topic. The results of this study show that marriage between relatives among the Batak Toba indigenous community abroad gives rise to two conditions, namely that the marriage is not recognized by the traditional leader and Dalihan Na Tolu because they still strictly uphold their customary law. However, under certain conditions, for example, if the marriage between relatives produces children, especially sons, then the marriage between relatives can be recognized on the condition that the married couple must carry out customary sanctions and pay a customary fine. If the marriage between relatives is recognized, the children born from the marriage can inherit their parents' (father's) property based on customary inheritance law. Conversely, if the marriage between relatives is not recognized, the children born from the marriage are not entitled to inherit based on customary inheritance law.